All-trans retinoic acid in hematologic disorders: not just acute promyelocytic leukemia - Chen, Yan; Tong, Xia; Lu, Rongyuan; Zhang, Zhengfu; Ma, Tao (Frontiers in Pharmacology, 2024)
All-trans retinoic acid (ATRA) plays a role in tissue development, neural function, reproduction, vision, cell growth and differentiation, tumor immunity, and apoptosis. ATRA can act by inducing autophagic signaling, angiogenesis, cell differentiation, apoptosis, and immune function. In the blood system ATRA was first used with great success in acute promyelocytic leukemia (APL), where ATRA differentiated leukemia cells into mature granulocytes. ATRA can play a role not only in APL, but may also play a role in other hematologic diseases such as immune thrombocytopenia (ITP), myelodysplastic syndromes (MDS), non-APL acute myeloid leukemia (AML), aplastic anemia (AA), multiple myeloma (MM), etc., especially by regulating mesenchymal stem cells and regulatory T cells for the treatment of ITP.ATRA can also increase the expression of CD38 expressed by tumor cells, thus improving the efficacy of daratumumab and CD38-CART. In this review, we focus on the mechanism of action of ATRA, its role in various hematologic diseases, drug combinations, and ongoing clinical trials.